A Study progress on moringa seed oil with microemulsion: bibliometrics analysis of year 2012-2023 - Lalu Muhammad Irham; Nining Sugihartini; chasanah, Uswatun; Sapto Yuliani (Universitas Muhammadiyah Malang, 2023)
Transdermal drug delivery systems increase the effectiveness of a drug substance, and one of them is a microemulsion. Moringa oil has anti-inflammatory, antioxidant, and antibacterial activity. The purpose of this study is to conduct a bibliometric analysis research on moringa oil formulated as microemulsions. A total of 5 English articles from the Scopus databases from 2012 to 2023 US sources were used in the bibliometrics analysis of Moringa oleifera seeds oil related to microemulsions. The bibliometrics analysis shows research trends, including the most used keywords depicted in visualizations using the VOSViewer application, article publishers, affiliations, and the author's country of origin. The most used keywords are microemulsions, microemulsion, Moringa oleifera, antioxidant activities, and antioxidants. The most publishers are Key Engineering Materials, the most affiliated are Chiang Mai University and Thamasat University, and most authors are from Thailand. The study of microemulsion formulations of Moringa seed oil has yet to be widely carried out but has been cited by other researchers.